WATER POLLUTION LEVELS IN THE SUWUNG ESTUARY, BALI, BASED ON BIOLOGICAL OXYGEN DEMAND - Ni Luh Gede Rai Ayu Saraswati; I Wayan Arthana; I Gede Surya Risuana; I Gede Hendrawan (BIOTROPIA, 2018)
Biological Oxygen Demand (BOD) is generally used for determining water pollution levels in bodies of water. An estuary is a semi-enclosed body of water that can be polluted via land areas or rivers. This study was conducted to determine the spatial distribution of water pollution levels in the Suwung Estuary in Bali based on BOD₅ analyses conducted in January and February 2016. Samples were taken at 20 points (19 points in the Suwung Estuary and 1 outside the Suwung Estuary as a control). BOD₅ samples were then analyzed in the laboratory. Our BOD₅ analyses used the amperometric method based on the National Field Manual for the Collection of Water-Quality Data, Chapter A7. BOD₅ samples were taken during all tidal cycles, from low to high tide and high to low tide. BOD₅ values ranged from 0.84 mg/L to 9.47 mg/L during low to high tide and from 0.96 mg/L to 8.75 mg/L during high to low tide. The BOD₅ concentration in the Suwung Estuary indicated slight contamination during both tidal conditions. The spatial distribution of BOD₅ concentration was higher around cage aquacultures, rivers, the Suwung Landfill, and near the Benoa Harbour.